(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: اشتملت هذه الدراسة على موضوع مهم من مواضيع العقيدة, وهو القلم الذي أمره الله عز وجل أن يكتب كل شيء, كما جاءت بذلك النصوص الشرعية, وهو من أمور الغيب التي يجب على المسلم الإيمان بها. فتطرقتُ في بداية المقال كالممهد له, بتوضيح المراد بالإيمان بالغيب, وبيان منزلته من العقيدة الإسلامية, وبعدها تحدثت عن أهم المسائل العقدية المتعلقة بالقلم؛ من توضيح المراد بالقلم, وبيان حقيقته, ثم إظهار أيهما أول المخلوقات القلم أم العرش ؟, ثم بيان شيءٍ من صفات القلم الواردة في النصوص الشرعية. وفي الأخير أنهيتُ المقال بخاتمة أجملتُ فيها نتائج البحث, والتي من أهمها: أن القلم حق, وأنه من أمور الغيب التي يجب الإيمان بها، وبما ثبت من صفاته، لا نتجاوز في ذلك النصوص الشرعية. كلمات دالة: القلم, المسائل, العقدية, المتعلقة, الغيب. Abstract: This study included an important topic of belief, which is the pen with which God Almighty writes the decrees of creatures, as stated in the legal texts, and it is one of the matters of the unseen that a Muslim must believe in. So I addressed at the beginning of the article as a precursor to it, clarifying what is meant by faith in the unseen, and clarifying its status in the Islamic faith, and then I talked about the most important doctrinal issues related to the pen; From clarifying what is meant by the pen, and explaining its reality, then showing which of the creatures is the first, the pen or the throne?, then clarifying some of the attributes of the pen mentioned in the legal texts. Finally, I ended the article with a conclusion in which I summarized the results of the research, the most important of which are: that the pen is true, and that it is one of the matters of the unseen that must be believed in, and with its proven qualities, we do not go beyond the legal texts. Key words : pen, issues, creedal, related, unseen.